Implementasi Teori Adaptasi Roy Untuk Meningkatkan Adaptasi dan Kepuasan Pasien Stroke: Studi Kualitatif - Eriyana; Fery Agusman; Any Rosiana M (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
Inability to adapt post-stroke significantly reduces a patient’s quality of life and healthcare satisfaction, necessitating holistic conceptual frameworks like Roy’s Adaptation Model (RAM) to support the recovery process. This study explored the implementation of RAM in supporting patient adaptation and its contribution to healthcare satisfaction within a stroke care unit. Employing a qualitative phenomenological design, data were gathered through in-depth interviews with nurses and supplemented by direct observations and triangulation with ward heads and patients' families. Thematic analysis revealed five major themes: (1) physiological adaptation via routine monitoring and multidisciplinary collaboration; (2) self-concept adaptation through empathy and psychosocial reinforcement; (3) role function adaptation via patient empowerment and family involvement; (4) interdependence adaptation through active family participation during recovery; and (5) enhanced patient and family satisfaction driven by therapeutic communication, continuous education, and holistic support. These findings suggest that RAM provides a valuable, structured framework for facilitating stroke adaptation, and its implementation in holistic nursing care contributes significantly to improving patient and family satisfaction with clinical services.